Towards Sustainable Society on Ubiquitous Networks The 8th IFIP Conference on e-Business, e-Services, and e-Society (I3E 2008), September 24-16, 2008, Tokyo, Japan - Oya, Makoto; Uda, Ryuya; Yasunobu, Chizuko; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of refereed international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Organized Session -- eService Innovation and Sensor Based Healthcare -- Research Track -- Decision Making Model for Online Music Service Users -- Intraday-scale Long Interval Method of Classifying Intramonth-Scale Revisiting Mobile Users -- The Study of Customer Segmentation Examined by Catastrophe Model -- A Procedure of How to Conduct Research in Transparent Mobile Recommendations -- Development of Recommender Systems Using User Preference Tendencies: An Algorithm for Diversifying Recommendation -- Cryptographic Approch for Workflow Systems -- A Fuzzy Model for Scalable Trust in E-Commerce -- Extending RBAC for Large Enterprises and Its Quantitative Risk Evaluation -- Presence-Based Runtime Composition of IMS Services Deployed in a SIP Servlet Platform -- A Service Oriented and Agent-Based Architecture for the e-Collaboration of SMEs -- Autonomous Web Services Based on Dynamic Model Harmonization -- A Nonlinear Representation of Page History in P2P Wiki System -- Distributed Secure Virtual File System Using FUSE -- Pricing for Maximizing Provider's Revenue in Multicast Content Delivery Services -- Personalized Public-Transport Guidance Using Mobile End Devices -- Internet Adoption in Tourism Industry in China -- The Use of Data Sources of Medication Information - a Finnish Primary Care Organization in the Light of National e-Health Scenarios -- Student Retention through Customized Service Processes -- e-Government in the Finnish Early Childhood Education: An Analysis of Current Status and Challenges -- Network-driven Context in User-driven Innovation -- Does E-government Trust in e-Commerce when Investigating Trust? A Review of Trust Literature in E-Commerce and e-government Domains -- Effects of Information Communication Technology on Urban and Rural Service Sectors: An Empirical Analysis of Japanese Economic Geography -- The Age-Divide in E-Government - Data, Interpretations, Theory Fragments -- Software Piracy in Chilean e-Society -- A Computing System to Assist Business Leaders in Making Ethical Decisions -- Industrial and Administration Track -- Local Government ICT Platform Standardization Activities of ICT Systems and Services for Offering High Value-added Service by Interacting Local Governments, Regional Institutions and Private Sector -- Service Interaction Platform Technologies Providing High Value-added ICT Services -- Realizing Interoperable Infrastructure for Electronic Business Systems and Local Government Systems -- Group Support in Collaborative Networks Organizations for Ambient Assisted Living.
Keywords: COMPUTER SCIENCE; COMPUTER COMMUNICATION NETWORKS; DATA PROTECTION; INFORMATION SYSTEMS; COMPUTER SCIENCE; COMPUTER COMMUNICATION NETWORKS; SYSTEMS AND DATA SECURITY; INFORMATION SYSTEMS AND COMMUNICATION SERVICE; COMPUTERS AND SOCIETY